1988
DOI: 10.1128/iai.56.8.1846-1857.1988
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the plasmid from Escherichia coli RDEC-1 that mediates expression of adhesin AF/R1 and evidence that AF/R1 pili promote but are not essential for enteropathogenic disease

Abstract: RDEC-1, an Escherichia coli strain that adheres to rabbit mucosa and causes an attaching, effacing lesion, expresses the pilus adhesin AF/Rl which determines in vitro attachment to rabbit intestinal brush borders. In order to determine the role of AF/Rl pili in the pathogenesis of enteropathogenic diarrhea in rabbits, we localized the genes for AF/Rl expression, constructed an AF/R1strain, and compared the virulence of the AF/ Rl and AF/R1strains with particular attention to the development of attaching, effac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 24 publications
4
50
0
Order By: Relevance
“…Next we examined the role of AF/RI pili in the binding measured by this assay. An RDEC-1 variant (M34) with the AF/R1 gene inactivated and therefore lacking AF/Rl (Wolf et al, 1988) pili, gave no binding above background . When the E. coli RDEC-1 were cultured under the standard conditions (aerated PAB), promoting expression ofAF/R1 pili, the binding, as expected, was not inhibited by mannose.…”
Section: Binding Ofe Coli Rdec1 To Brush Borders Mediated By Af/ri Pilimentioning
confidence: 99%
See 1 more Smart Citation
“…Next we examined the role of AF/RI pili in the binding measured by this assay. An RDEC-1 variant (M34) with the AF/R1 gene inactivated and therefore lacking AF/Rl (Wolf et al, 1988) pili, gave no binding above background . When the E. coli RDEC-1 were cultured under the standard conditions (aerated PAB), promoting expression ofAF/R1 pili, the binding, as expected, was not inhibited by mannose.…”
Section: Binding Ofe Coli Rdec1 To Brush Borders Mediated By Af/ri Pilimentioning
confidence: 99%
“…The metabolically labeled bacteria were washed with PBS and resuspended in PBS containing 1% BSA and 0.15 M mannose before use. M34 is a variant of RDEC-1 in which the plasmid-encoded gene for AF/RI pili has been inactivated by transposon mutagenesis (Wolf et al ., 1988) .…”
Section: Chemicalmentioning
confidence: 99%
“…2a) appears to be necessary for initial signalling leading to the development of the AE lesion, but the mediators of this attachment are poorly understood. Studies have shown a potentiating effect of adhesion factors (such as the EPEC Adherence Factor [EAF] plasmid and the REPEC-associated AF/R1 fimbrial adhesin) upon AE lesion formation in vitro (Knutton et al, 1987;Francis et al, 1991) and on AEEC virulence in vivo (Levine et al, 1985;Wolf et al, 1988). The EAF plasmid contains a gene cluster (bfp) encoding bundle-forming pili (BFP) (Stone et al, 1996), which mediate microcolony formation in culture and localized adhesion to HEp-2 cells (Giron et al, 1991).…”
Section: Stage 1: Initial Non-intimate Attachmentmentioning
confidence: 99%
“…For example, weanlingassociated REPEC O15 is reported commonly from Belgium, the Netherlands and North America, but less commonly from France and Spain (Blanco et al, 1996). REPEC O15:H-includes the prototypical strain RDEC-1 (Cantey and Blake, 1977; that encodes a plasmidborne rabbit-specific fimbrial adhesin, termed AF/ R1, which mediates non-intimate adhesion to ileal M cells and is an established virulence factor (Berendson et al, 1983;Wolf et al, 1988). RDEC-1 also elaborates a soluble factor which affects the electrical properties of rabbit ileal mucosa in vivo and may therefore have diarrhoeagenic properties (Raimondi et al, 2001).…”
Section: Rabbitsmentioning
confidence: 99%
“…Both RDEC-1 and EPEC express pili necessary for initial attachment of the bacteria to mucosal surface. RDEC-1 express AF/Rl pili [22] and EPEC strains produce bundle-forming pili [23]. The AE lesion produced by RDEC-1 is indistinguishable from that produced by human EPEC [ 1, lo].…”
Section: Introductionmentioning
confidence: 99%